Collaboration in Implementation of Bantuan Stimulan Perumahan Swadaya Pontianak City - Verdico Arief (Iapa Proceedings Conference, 2018)
Bantuan Stimulan Perumahan Swadaya masyarakat (BSPS) is a government provided assistance to help renovate uninhabitable homes for low income communities. Pontianak City Government has implemented this program since several years ago. But in the implementation there is still a problem, the cause of problem is because in implementing this activity involves many parties who have different perception and create discretion in different decision making thereby impeding the implementation of program. It causes the implementation of program to be inhibited. For that it’s interesting if conducted a study to examine how collaboration in implementation of Bantuan Stimulan Perumahan Swadaya Pontianak City. Research was conducted qualitatively with descriptive approach using case study technique, using the collaborative theory proposed by Russell M. Linden. From the results of this research will be obtained solution of the problems and collaboration model.